A study into the evolution of bank capital in South Africa (1994-2010) - West, Martin (School of Economics, 2015)
The period 1994 to 2010 has seen marked changes in both the capital and reporting requirements for banks globally. In South Africa, Basle I was in effect in 1994, whilst Basle II came into being in 2008, both of which placed new requirements on banks in terms of the calculation of their capital positions. During 1999 the South African Reserve Bank ("SARB") moved from a policy of direct controls to inflation targeting.